The Influence Of Classical Music Therapy To Decrease Blood Pressure Of Patients With Hypertension In The Elderly - Christine Aden; Barto Mansyah; Berthiana .T (International Journal of Health and Pharmaceutical (IJHP), 2022)
Hypertension is often referred to as the “silent killer”, because often attack the elderly (elderly) without feeling something and unwittingly patients experience complications. One way to control blood pressure in hypertensive patients, namely the use of therapeutic interventions nonpharmacological. Reduce hypertension therapeutic uses nonpharmacological, one of classical music therapy. The purpose of Research To know the influence of classical music therapy to decrease blood pressure of patients with hypertension in the elderly. Research methods: Literature review, the database used is Google Scholar. The search is performed in the month (August-September 2021) which can be accessed full text in pdf format and scholary. The results of the identification on the third article found various categories of hypertension before the intervention, namely on the first journal the majority of hypertension in the category of mild hypertension by as much as 23 respondents (76,6%). In the journal of the second majority of high blood pressure as much as 19 respondents (of 63.3%). On the journal third majority of hypertension in the category of hypertension II degree as much as 9 respondents (53%). Based on the three articles that the author found there are differences in the categorization of hypertension. Not explained in detail about the categorization is along with blood pressure values in the article that have been identified so that the author can not be mensimilarkan or leveler category of hypertension. Of the three articles that have been identified there is a decrease in blood pressure after therapy is given to classical music with a duration of 15-30 minutes and found different variations of hypertension in the third article. Based on the results of the analysis of the article consists of 3 article there is the influence of classical music therapy to decrease blood pressure of patients with hypertension in the elderly.